Radiative properties of Cu-isoelectronic As, Se, and Br ions for astrophysical applications. Issue 2 (28th January 2022) - , Jyoti; Kaur, Harpreet; Arora, Bindiya; Sahoo, B K
ABSTRACT: We present precise radiative data of line strengths, transition probabilities, and oscillator strengths for the allowed transitions among the nS 1/2, nP 1/2, 3/2, n ′ D 3/2, 5/2, and n ′ F 5/2, 7/2 states with n  = 4 to 6 and n ′ = 4, 5 of the Cu-isoelectronic As, Se, and Br ions. Due to unavailability of precise observations of these spectroscopic data, their accurate estimations are of great interest and useful in analysing various astrophysical phenomena undergoing inside the heavenly bodies that contain As, Se, and Br elements. An all-order perturbative many-body method in the relativistic theory framework has been employed to determine the atomic wave functions, which are further used to estimate the above quantities with the uncertainties. We found significant differences between some of our results and results that are available earlier.